Borders and mobility control in and between empires and nation-states - Pešalj, Jovan; Steidl, Annemarie 1965-; Lucassen, Leo 1959-; Ehmer, Josef 1948-2023 (Brill, 2023)
In a modernist interpretation of migration controls, nation states play a major role. This book challenges this interpretation by showing that comprehensive migration checks and permanent border controls appeared much earlier, in early modern dynastic states and empires, and predated nation states by centuries. The 11 contributions in this volume explore the role of early modern and modern dynastic kingdoms and empires in Europe, the Middle East and Eurasia and the evolution of border controls from the 16th to the 20th century. They analyse how these states interacted with other polities, such as emerging nations states in Europe, North America and Australia, and what this means for a broader reconceptualization of mobility in Europe and beyond in the longue duree. Contributors are: Tobias Brinkmann, Vincent Denis, Sinan Dincer, Josef Ehmer, Irial A. Glynn, Sabine Jesner, Olga Katsiardi-Hering, Leo Lucassen, Ikaros Mantouvalos, Leslie Page Moch, Jovan Pesalj, Lewis H. Siegelbaum, Annemarie Steidl, and Megan Williams
Keywords: Geschichte 1500-1914; Grenze; Einwanderungspolitik; Nationalitätenstaat; Nationalstaat; Grenzpolitik; Grenzpolizeiliche Kontrolle; Migrationspolitik; Geschichte; HISTORY / Social History; History; SOCIAL SCIENCE / Ethnic Studies / General; Social & cultural history; Sozial- und Kulturgeschichte; Aufsatzsammlung